Regulation of the RNA-dependent protein kinase by triple helix formation - Vuyisich, Momchilo (Oxford University Press, 2000)
The RNA-dependent protein kinase (PKR) is an interferon-induced, RNA-activated enzyme that phosphorylates the α-subunit of the translation initiation factor eIF-2, inhibiting its function. PKR is activated in vitro by binding to double-stranded RNA (dsRNA) molecules of ~30 bp or longer. Here we show that triple helix forming oligonucleotides (TFOs) inhibit dsRNA binding to the isolated RNA binding domain of PKR. The inhibition is specific to the targeted RNA and dependent on TFO length. Binding to a 30 bp duplex is inhibited by a 28 nt TFO and a 20 nt TFO with an IC(50) of 35 ± 2 and 210 ± 22 nM, respectively. An 18 nt TFO partially inhibits binding. The activation of the kinase domain of PKR by a 30 bp RNA duplex is also inhibited by a 28 nt TFO. Inhibition of binding is most effective when the triple helix is formed prior to addition of the protein. These results indicate that triplex formation can be used to prevent the binding of an RNA binding protein with dsRNA-binding motifs.